Respuesta :

aachen

Answer:

option B is correct, i.e. (f+g)(x) = x² + 3x - 5.

Step-by-step explanation:

Given f(x) = 3x + 1.

Given g(x) = x² - 6.

To find (f+g)(x).

The rule of Arithmetic of functions is:- (f+g)(x) = f(x) + g(x).

(f+g)(x) = (3x+1) + (x²-6).

(f+g)(x) = x² + 3x + 1 - 6.

(f+g)(x) = x² + 3x - 5.

Hence, option B is correct, i.e. (f+g)(x) = x² + 3x - 5.

Answer:

Choice B is correct answer.

Step-by-step explanation:

We have given two functions.

f(x) = 3x+1    and g(x) = x²-6

We have to find the sum of given two functions.

(f+g)(x) = ?

The formula to find the sum of two functions:

(f+g)(x) = f(x) + g(x)

Putting the given values of functions , we have

(f+g)(x) = 3x+1 + x²-6

Adding like terms , we have

(f+g)(x) = 3x+x²-5

Rearranging, we have

(f+g)(x) = x²+3x-5  which is the answer.